Assessing people's perceptions of forests: research in West Kalimantan, Indonesia - Colfer, C.J.P.; Woelfel, J.; Wadley, R.L.; Harwell, E. (Resources for the Future and Center for International Forestry Research, 2001)
Previous research has identified three important issues of relevance to forest people’s roles in sustainable forest management that this article addresses here: the presence of a “conservation ethic”, a feeling of closeness to the forest, and a significant forest-culture link. It provides the results of a method (the Galileo) that is hoped could help clarify these issues and render them more quantitatively assessable. Instead, it was found that the method more useful in reflecting local perceptions of the forest. The differences in perceptions based on gender and ethnicity are of interest for forest management more generally.